Pure Premium Modeling for Property Fire Insurance Using Monte Carlo Method - Putri, Linda Damayanti; Firdaus, Muhammad Rayhan (International Journal of Mathematics, Statistics, and Computing, 2024)
Modeling pure premium of property fire insurance is an important aspect for insurance companies in managing risk. This article discusses the Monte Carlo method in modeling pure premium of property fire insurance. The Monte Carlo method is used to simulate various scenarios and loss factors due to property fire. Monte Carlo simulation offers an effective approach to modeling property fire risk. The results of this study are expected to provide an overview of the modeling of pure premium of property fire insurance and assist insurance companies in decision making and determining optimal premium prices.